Patterns of Heat Strain Among a Sample of US Underground Miners. Issue 3 (March 2019) - Yeoman, Kristin; DuBose, Weston; Bauerle, Timothy; Victoroff, Tristan; Finley, Seth; Poplin, Gerald
Abstract : Objective: This study characterizes physiological measures of heat exposure among US underground miners. Methods: Core body temperature measured by using ingestible sensors during subjects' normal work shifts was categorized into four temperature zones: less than 37.5 °C, 37.5 °C to less than 38 °C, 38 °C to less than 38.5 °C, and more than or equal to 38.5 °C. Results: On average, subjects changed temperature zones 13.8 times per shift. Temperatures increased above the recommended limit of 38 °C nearly 5 times per shift for an average of 26 minutes each episode. Conclusions: Unlike previous heat stress research that reported only maximum and mean temperature measurements, this analysis demonstrates a dynamic pattern of physiologic heat strain, with core body temperatures changing frequently and exceeding the 38 °C limit multiple times per shift. Further research is needed on the impact of multiple short-term, intermittent heat exposures on miners.